A mixed methods case study examination of the role of the therapeutic alliance in EMDR within primary care - Skinner, D.J. (2017)
The therapeutic relationship within psychotherapy is well recognised as a pertinent component of successful treatments. In particular, the alliance component of the therapeutic relationship has demonstrated a moderate and robust correlation to positive outcomes. The alliance is considered the change mechanism within the more relationally focused therapies (e.g., psychodynamic). In contrast, therapies that focus on specific techniques related to underlying theory regarding the development and amelioration of mental health difficulties, prioritise the protocols as the change mechanism.